Extended Cervicomediastinal Thymectomy in the Integrated Management of Myasthenia Gravis - Gregory B. Bulkley; Kirsten N. Bass; G. Stephenson; Marie Diener‐West; Simeon George; Patrick A. Reilly; R. Robinson Baker; Daniel B. Drachman (1997)
Objective The authors evaluated the response to extended cervicomediastinal thymectomy as a component of the integrated management of patients with myasthenia gravis in a large series of patients from a single institution. The authors evaluated the response to therapy with respect to a graded, multivariate, ordinal scale chosen to reflect the full range of the disease's manifestations. Summary Background Data A number of series, of varying sizes, describe the response of patients with myasthenia gravis to thymectomy primarily with respect to the bivariate endpoint of the presence or absence of "remission." These studies fail to describe the full spectrum of postoperative disease severity and have been unable to quantify definitively the influence of putative prognostic variables, nor to assess definitively the statistical significance of apparent improvements over time. Methods The authors evaluated 202 consecutive patients who underwent trans-sternal thymectomy for symptomatic myasthenia gravis from 1969 through 1996 at the Johns Hopkins Hospital. The response to surgery, combined with postoperative medical therapy, was evaluated by a standardized scale reflecting the full spectrum of the disease. These data were analyzed by a novel mean multivariate regression analysis, which allowed the quantification of the statistical significance of apparent responses over time and the evaluation of the independent influence of each of nine putative prognostic indicators. Results There was no perioperative mortality and a 33% perioperative morbidity. There was a marked clinical response at 6 months to 1 year after surgery that was sustained for at least 10 years thereafter. The median increment of improvement was two (of five) classes. Eighty-six percent and 83% of the patients had improved by at least one class at 5 and 10 years, respectively. These changes were statistically significant (p < 0.001). Whereas the use of extended cervicomediastinal thymectomy was associated with a greater than twofold chance of improvement, compared to conventional trans-sternal thymectomy, neither the pathologic diagnosis (presence of thymoma) nor the age at surgery proved to be negative predictors of postoperative response. Conclusions Extended cervicomediastinal thymectomy is the procedure of choice as a component of the integrated management of myasthenia gravis, with significant improvement seen in the group as a whole, as well as in subgroups of patients with thymoma and those older than 40 years of age.